Analisis Kesesuaian dan Daya Dukung Ekowisata Mangrove Teluk Urfu, Kabupaten Biak Numfor - Rumbiak, Kristhopolus K.; Rejauw, Korinus; Dimara, Lisiard (Cenderawasih University, 2023)
Urfu Bay is a relatively new marine tourism destination and quite a favorite among the people of Biak Numfor. The Tourism Awareness Group (POKDARWIS) of Urfu Village is developing mangrove tourism. At the same time, scientific data is not yet available on the area's suitability level and the environment's carrying capacity for mangrove tourism activities. Hence, this research must be carried out to support the sustainable management of Urfu Bay mangrove tourism. The objectives of this study are: (1) knowing the tourism suitability index (IKW); and (2) knowing the carrying capacity of the Urfu Bay mangrove ecosystem (DDK). The study time is six months, which is April to September 2023. This research is located in the mangrove ecosystem of Urfu Bay, Biak Numfor Regency. The research method used is a survey, while random sampling techniques, observation, interviews, and literature studies carry out data collection. The results showed that the mangrove ecosystem of Urfu Bay: (1) Very suitable as a mangrove tourism area with a tourism suitability index (IKW) value of 2.85; and (2) Has an Area Carrying Capacity (DDK) of 381 people per day. This study concludes that the mangrove ecosystem of Urfu Bay is very suitable and prospective for developing mangrove tourism.